Participatory arts in international development - Soria-Donlan, Ines; Cooke, Paul 1969- (Rethinking development, 2020)
"This book explores the practical delivery of participatory arts projects for international development. Bringing together an interdisciplinary group of academics, international development professionals and arts practitioners, the book engages honestly with the competing challenges faced by the different groups of people involved. Participatory arts are becoming increasingly popular in international development circles, fuelled in part by the increased accessibility of audio-visual media in the digital age, and also by the move towards participatory discourses in the wake of the UN's Agenda 2030. The book asks: - What do participatory community arts projects look like in practice, and why are they used as an international development tool? - How can we develop practical and sustainable development projects on the ground, localising best practice according to cultural, economic and linguistic contexts? - What are the enablers of, and barriers to, successful participatory initiatives, and how can we evaluate past projects to learn, and feed into future projects? Written to appeal both to academics and practitioners, this book would also be suitable for teaching on courses related to participatory development, community arts, and culture and development"--